Adaptation in rice production in the frequently flooded areas of rural Thailand : a case study of Khon Khean Province - Phakamon Srikamta; Ahmad, Mokbul Morshed; Thapa, Gopal B.; Soparth Pongquan; International Fellowships Program Ford Foundation, USA; AIT Fellowship (Pathum Thani : Asian Institute of Technology, 2013)
This research involved the adaptation strategies of farmer in rice production in the frequently flooded areas of rural Thailand: a case study of the Khon Khean Province. The thesis also assesses in social, economic and environmental benefits of rice production adaptation strategies. The main objective of this study was to study the effect of food on rice production and then to examine adaptation strategies in rice production system applied during flood and to study the change in rice production systemand its effect on farmer{u2019}s socioeconomic and environmental conditions. The farmer adaptationin this research included 92rural farmer householdsin Moung -Pia sub -district , Ban -Pai district , Khon Khean Province.A standardized questionnaire collectsdata as a prime tool and was supplemented by interviews and a group discussion. Theresearch was mainly focused on a quantitative analysis but with support of qualitative analysis. The main findingof this research showed the main pattern of adaptation at farm level. There is an individual and direct adaptation in rice production. The flood is the stimuli of adaptation in rice seeds because the farmer concerns about the shot takeof the food security problem. The strategy adaptation begins with the change is rice seeds wasleadto changesin crop calendar. Moreover, farmer can adapt farm management whichfactor of production. They are decreasing the cost of production. Findingthe new areas which support a cultivationin dry season.The farmer also findsknowledge for support adaptation.Moreover, the farmernot only cultivate only one crop but also they have an alternate occupation fordiversification which alternate way for improving more incomein a flood area. The socioeconomic affectedby adaptation in rice production lead tothe increasing rice cultivation for purchasebecause the maximum of production more than consumption and increasing time for cultivation. Rice for purchase lead to theincreasing income.Moreover , There are increasing the sufficiency of rice for consumptionand close the gap about the food shortage problem. The increasing labor utilizationis also impacted by rice cultivation because the farmer needsto decrease the investment couple with the comforteror farm processing. Inthe environmental effected, Althougthfarmer hasknowledgein organic using fertilizerbut there are not increasing soil quality because the incomplete degradation in the farmby cultivation 2 timesper year. There are still affectedin water animalsby spinningand chemical pesticide and herbicide.Moreoverfarmer still has effected by chemical washingeven they know about self protection. Theyare directly affectedby the herbicide.At the same time the trend of rice production still increasing because the price factor is the incentivefor production.The recommendations were given to suggest involvedthe institutionto support for flooding solution and water for irrigation. Promotingthe new rice system which suitable to cultivate in a flood plain and allied with the environmental system.Promoting the diversification crop and occupation for improving income and Building capacity in farmer group for planning adaptation.
Submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Thesis (M. Sc.) - Asian Institute of Technology, 2013
Keywords: Agricultural production; Rice -- Thailand -- Khon Khean